PENGUJIAN MODEL FISIK TERHADAP KARAKTERISTIK HIDRAULIK AKIBAT PEMASANGAN GROUNDSILL PADA SALURAN PEMBAWA BANGUNAN PELIMPAH BENDUNGAN PIDEKSO - Krisna Sulistya; Indrawan Indrawan; Ignatius Sriyana (Politeknik Negeri Semarang, 2022)
Pidekso Dam is located in Pidekso Village, Wonogiri Regency, Central Java Province. The Pidekso Dam Spillway Building mode test was carried out to verify any deficiencies or design errors that might occur. One of the scope works in spillway model is a carrier channel downstream of the spillway which is 360 m long. To overcome the scour that occurs in the carrier channel downstream of the spillway, in the 4th series test, a groundsill structure was installed as a basic stabilizer for the carrier channel. The method is used in modelling include physical modelling, drainage testing, and observation of water flow and scouring that occurs at the bottom of the channel. The carrier channel groove model and the groundsill structure are made with a 1:40 scale both upright and flat (without distortion). The model test shows that the water flow in the carrier channel upstream of the groundsill is even and uniform with the bottom material of the channel not moving. At the bottom of the channel on the outer side of the bend which is assumed to be granular material, it is scoured to a depth of 2.68 m on the Z9 profile. This profile needs to be protected by rip-rap of concrete blocks, unless the base of the existing channel is a hard bedrock.